2018
DOI: 10.1016/j.ajodo.2017.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of different radiographic methods for the localization of displaced maxillary canines

Abstract: Conventional radiographic methods demonstrated a more subjective diagnostic procedure compared with CBCT images. CBCT is a more accurate and precise examination method compared with conventional radiography for the localization of impacted teeth and root resorption of the adjacent teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 28 publications
1
18
0
7
Order By: Relevance
“…Um estudo, comparando imagens radiográficas e tomográficas, concluiu que a TCFC foi o método mais confiável e preciso para diagnóstico da localização de caninos superiores inclusos, bem como da presença de reabsorção radicular nos dentes adjacentes. 5 Neste estudo, encontrou-se em 61,9% dos casos a coroa do canino localizada por palatina; em 14,3%, por vestibular; e em 23,8%, a coroa apresentava-se centralizada no rebordo alveolar, corroborando com outros estudos que encontraram de 80% a 90% dos caninos inclusos por palatina. 27,29,30 A reabsorção dos dentes adjacentes pela impactação dos caninos tem sido relatada como resultado do efeito físico do contato entre o canino incluso e o dente adjacente, devido à pressão ativa durante a erupção.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Um estudo, comparando imagens radiográficas e tomográficas, concluiu que a TCFC foi o método mais confiável e preciso para diagnóstico da localização de caninos superiores inclusos, bem como da presença de reabsorção radicular nos dentes adjacentes. 5 Neste estudo, encontrou-se em 61,9% dos casos a coroa do canino localizada por palatina; em 14,3%, por vestibular; e em 23,8%, a coroa apresentava-se centralizada no rebordo alveolar, corroborando com outros estudos que encontraram de 80% a 90% dos caninos inclusos por palatina. 27,29,30 A reabsorção dos dentes adjacentes pela impactação dos caninos tem sido relatada como resultado do efeito físico do contato entre o canino incluso e o dente adjacente, devido à pressão ativa durante a erupção.…”
Section: Discussionunclassified
“…Com a TC, o ortodontista pode ter informações diagnósticas que não poderiam ser obtidas por exames radiográficos, influenciando diretamente a tomada de decisão clínica. 5 O tratamento de caninos inclusos depende de cada caso. Se o paciente optar pelo não tratamento, o acompanhamento longitudinal deve ser criteriosamente realizado.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In this technique, two periapical radiographies are taken with different ray angles, and it is determined whether the impacted tooth is labial or palatal to the roots of the incisors (21). Apart from the parallactic technique, panoramic radiography and/or panoramic radiography along with lateral cephalometric radiography can be used (22,23). However, in CT operations, it was found that the positions of the impacted teeth and pathologies they caused were much different from the aforementioned techniques (24).…”
Section: Evaluation Of Impacted Teeth and Oral Anomaliesmentioning
confidence: 99%
“…CBCT data can be reconstructed by software to measure and simulate an operation with a 3D model. Compared with traditional 2D measurements, CBCT is a more accurate detection method 13 …”
Section: Introductionmentioning
confidence: 99%